Christen Christensen Nestvedensis: Præst på Gotland 1616 - 1656 - Jensen, Jørgen (Kirkehistoriske Samlinger, 1995)
In the church of Faro, just north of Gotland, a memorial tablet commemorates the rescue of twelve seal hunters, who had been adrift on an ice floe for two weeks in the winter 1602/1603. On the tablet is an account of the incident, in verse, and a short hymn of thanksgiving, both in Danish. The author of both poem and hymn was probably Christen Christensen Nestvedensis, and they are his only known surviving literary works. He was vicar at Faro from 1616 - 1620. In 1620 he moved to the parish of Oja in southern Gotland, where he was vicar until his death in 1656. Also at Oja evidence of his interest in art can be seem. A new pulpit and an altar decoration of local sandstone was donated by Christianus Christiani et uxor ejus. At the peace of Bromsebro in 1645, Gotland, which had been Danish for nearly 300 years, was surrendered to Sweden for thirty years. Except for the years 1676 - 1679, during the Scanian War, Gotland has remained Swedish. Like most of the vicars in the ceded province, Christen Christensen chose to remain in his parish under Swedish rule. The careers of Christen Christensen and three of his sons, who were also vicars of parishes on Gotland, and of the Danish superintendent (bishop) of Gotland, Hans Nielss0n Strelow, illustrate the change from Danish to Swedish as the language of the church. Strelow, who was appointed Swedish superintendent in 1646, suceeded in making the moderate Swedish church policy yet more moderate by a combination of flexibility and - when he deemed it necessary - stubbornness. Two of the Christensen brothers got permission of the Swedish authorities to continue to preach in Danish as late as 1687.